Theoretical Investigation of the Deactivation of Ni Supported Catalysts for the Catalytic Deoxygenation of Palm Oil for Green Diesel Production - Hafeez, Sanaa; Al-Salem, Sultan M.; Papageridis, Kyriakos N.; Charisiou, Nikolaos D.; Goula, Maria A.; Manos, George; Constantinou, Achilleas (My University, 2021)
For the first time, a fully comprehensive heterogeneous computational fluid dynamic (CFD) model has been developed to predict the selective catalytic deoxygenation of palm oil to produce green diesel over an Ni/ZrO2 catalyst. The modelling results were compared to experimental data, and a very good validation was obtained. It was found that for the Ni/ZrO2 catalyst, the paraffin conversion increased with temperature, reaching a maximum value (>95%) at 300◦CHowever, temperatures greater than 300◦C resulted in a loss of conversion due to the fact of catalyst deactivation. In addition, at longer times, the model predicted that the catalyst activity would decline faster at temperatures higher than 250◦C. The CFD model was able to predict this deactivation by relating the catalytic activity with the reaction temperature.
Keywords: Green diesel; Catalyst deactivation; Selective deoxygenation; Computational fluid dynamics (CFD)